Comparative Analysis of Stability to Induced Deadlocks for Computing Grids with Various Node Architectures - Tatiana R. Shmeleva (Моделирование и анализ информационных систем, 2018)
In this paper, we consider the classification and applications of switching methods, their advantages and disadvantages. A model of a computing grid was constructed in the form of a colored Petri net with a node which implements cut-through packet switching. The model consists of packet switching nodes, traffic generators and guns that form malicious traffic disguised as usual user traffic. The characteristics of the grid model were investigated under a working load with different intensities. The influence of malicious traffic such as traffic duel was estimated on the quality of service parameters of the grid. A comparative analysis of the computing grids stability was carried out with nodes which implement the store-and-forward and cut-through switching technologies. It is shown that the grids performance is approximately the same under work load conditions, and under peak load conditions the grid with the node implementing the store-and-forward technology is more stable. The grid with nodes implementing SAF technology comes to a complete deadlock through an additional load which is less than 10 percent. After a detailed study, it is shown that the traffic duel configuration does not affect the grid with cut-through nodes if the workload is increases to the peak load, at which the grid comes to a complete deadlock. The execution intensity of guns which generate a malicious traffic is determined by a random function with the Poisson distribution. The modeling system CPN Tools is used for constructing models and measuring parameters. Grid performance and average package delivery time are estimated in the grid on various load options.